OBITUARY: In Memoriam Prof Maríe Muller (The Strategic Review for Southern Africa, 2020)
The well-known political scientist, Maríe Muller, passed away on 4 March this year after a five-year battle with Multiple System Atrophy (MSA), a degenerative neurological disorder. Maríe had a long and distinguished career in the South African and broader international Political Sciences communities. She obtained her BA, BA Hons and MA in International Relations with distinction from the University of Pretoria (UP), and her PhD from the (then) Rand Afrikaans University. She joined the Department of Political Sciences at the University of South Africa (UNISA) during the 1970s and became one of the first female International Relations lecturers in South Africa. She was a warm and lovely person who will be remembered for her integrity, commitment and her loyalty to friends, colleagues and students. She is survived by her husband, Andre Viljoen and her three children, Frans, Liebet and Daniel Jooste. This issue of the Strategic Review for Southern Africa is dedicated to her memory.Hamba Kahle, Maríe.
Keywords: political scientist; Maríe Muller; passed away